A Geologist Æs Guide to Destroying Shareholder Value and a Business Improvement Model to Insure Against it (The Australasian Institute of Mining and Metallurgy, 2002)
Many aspects of best practice resource evaluation do not create value, but poor practice can certainly destroy value. Generally companies prefer to present how their good practice adds value and for this reason few publications exist on examples of how poor practice can destroy value. However in big and small companies there are many previous and current examples of poor practice destroying value. The incremental expenditure required to move from poor practice towards best practice can be looked upon as insurance against destroying shareholder value. Examples of how poor practice in geology has destroyed value are presented as well as the improvement model used by BHP Billiton to add value and insure against destroying value.